Of Grim Witches and Showy Lady-Devils: Wealthy Women in Literature and Film - Schuchter, Veronika (Text Matters: A Journal of Literature, Theory and Culture, 2019)
Imagining super rich women in the real and fictional world has long been a struggle. Those few depictions that do exist are scattered across time periods and literary genres, reflecting the legal restrictions that, at different points in time, would not allow women to accumulate assets independent of the patriarchal forces in their lives. The scarcity of extremely wealthy women in literature and film is confirmed by Forbes magazine’s list of the fifteen richest fictional characters that features forty different fictional men and only nine women, with never more than two female characters nominated in a single year. This article explores the depiction of three exceptionally wealthy women: Cruella de Vil in The Hundred and One Dalmatians (1956) by Dodie Smith, Miss Havisham in Great Expectations (1861) by Charles Dickens, and the figure of the stepmother in various adaptations of “Cinderella.” I demonstrate how the protagonists’ wealth allows them to manipulate others and disconnect themselves from patriarchal and societal expectations. Further, I argue that these affluent antagonists are “rogued” by their respective narratives, highlighting their perceived anti-feminine and emasculating behaviour resulting in a mode of narration that greedily gazes at and shames their appearances and supposed unattractiveness. While this genealogy of rich rogues reiterates the narrow scope of imagining wealthy women on the page and on the screen, there are moments in the narratives that disrupt stereotypical depictions of these wealthy characters who defy the labels imposed on them.